Evaluation of clinical outcomes in neuropathic pain with combinations of anti-neuropathic drugs - Pasha, Shaik A.; Vidyadhara, S.; Kalyan, M. Raghava; Sri, Lakshmi Banu; Keerthi, N.; Harshitha, A.; Sravani, K.; Haribabu, Ramineni (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Much of the pharmacological treatment modalities especially individual drugs for treating neuropathic pain have unwanted side effects, multiple day to day dosing, modest efficacy of topical treatments, and their local side effects. Combination drug regimen has the advantage of offering relatively better pain relief at lower drug doses and lesser side effects. Methods: The study was conducted in the Department of Neurology at NRI General Hospital, Guntur. The patients who met the inclusion and exclusion criteria were enrolled and assigned into 3 groups of the study drug combinations. The baseline characteristics and post interventional scores of Toronto Clinical Scoring System (TCSS), visual analogue scale (VAS), Hamilton Anxiety Rating Scale (HAM-A), Hamilton Depression Rating Scale (HAM-D) and Medical outcome of sleep scale (MOS) and were analyzed using t test and mean difference. Results: A statistically significant reduction in neuropathic pain in all the three groups was found. The mean difference between the baseline and post interventional scores of TCSS and VAS of group I, II and III were 2.97, 2.75, and 1.97; 2.32, 1.12, and 0.95 respectively. There was a statistically significant improvement of HAM-A in all the three groups, HAM-D and MOS sleep scale were found significant only in group II. Conclusions: The study findings revealed that all the three drug combinations were effective in the management of neuropathic pain with pregabalin and oxcarbazepine combination being better with respect to efficacy and tolerability. Regarding the treatment of depression and sleep disturbances associated with NP pregabalin and duloxetine was more effective.